(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2017)
In this paper ,we have dealt with the concepts of fuzzy generalized b- irresolute (in short fgb-irresolute ),fuzzy strongly generalized b-compact (in short fstg-b-compact ) and fuzzy generalized b-continuous (in short fgb-continuous ) functions , and find that every fgb-irresolute function is fgb-continuous and the converse is not true in general .We have also remember the concept of fuzzy -space ( f-space ) and we have proved that every fuzzy generalized b-compact ( in short fgb-compact ) subset of an f-space is fuzzy generalized b-closed ( in short fgb-closed ) , and if isn’t f- space , then need not that every fgb-compact set is fgb-closed . Finally we defined compactly fuzzy generalized b-closed ( in short compactly fgb-closed ) set and proved that every fgb-closed subset of a spaceis compactly fgb-closed .